Pengaruh Social Capital dan Human Capital Terhadap Business Growth Pengusaha Perempuan di Jakarta dan Tangerang [Effect of Social Capital and Human Capital on Business Growth of Women Entrepreneurs in Jakarta and Tangerang] - Hutabarat, Zoel; Dini, Shania Jusan (Universitas Pelita Harapan, 2021)
The aim of this study is to examine the positive effect of social capital, human capital, reputational capital on business growth on women entrepreneurs in Jakarta dan Tangerang. Intangible assets are widely regarded as a key success factor for business growth in various countries. The growth of women's businesses in developing countries is still rare to find, but in recent years women have been seen to be more active in terms of entrepreneurship and business with women's ownership continues to grow to this day. This study uses a quantitative approach. The data collection technique in this study used an electronic questionnaire via Google Form, consisting of 31 indicators and the number of respondents was 201 respondents who are women and currently have businesses. The analytical method used in this research is SmartPLS 3.0, and in distributing the questionnaire, this study uses judgment sampling technique. The results of this study conclude that social capital has a positive effect on business growth, human capital has a positive effect on business growth, individual reputation capital has a negative effect on business growth, and organization reputational capital has a positive effect on business growth.